The Concept of Women's Education from the Perspective of Raden Ajeng Kartini: The Role of Mothers as Al-UMM Madrasatul Ula in Forming a Superior Generation - Wirdatul Hasanah; Akhmad Zaeni; Siti Muthiatun Najiyah; Siti Aminah; Diah Ainun Khafidloh (Penerbit Hellow Pustaka, 2026)
This study aims to deeply analyze the concept of women’s education from the perspective of Raden Ajeng Kartini and its relevance to the role of mothers as al-umm madrasatul ula in shaping superior generations. The background of this research is based on the importance of women’s education as a fundamental pillar in developing high-quality human resources. This research uses a qualitative approach with a library research method by examining Kartini’s works, especially Habis Gelap Terbitlah Terang, along with Islamic education literature and relevant academic journals. The data analysis technique is descriptive-analytical by reviewing, comparing, and integrating various relevant concepts. The results show that Kartini had a progressive view on the importance of women’s education as a means of empowerment and national progress. In Islamic perspective, the concept of al-umm madrasatul ula emphasizes that mothers are the first and primary educators who play a crucial role in shaping children’s character, morality, and intellectual development. The integration of Kartini’s ideas and Islamic educational concepts indicates that women’s education is not only a right but also a strategic necessity in creating superior generations who are intellectually, emotionally, and spiritually balanced with strong moral values.